Incidence of Stunting: Early and Exclusive Breastfeeding in Two-Year-Old Children - Hartono, Rudy; Yuridesi Nurani Putri; Sunarto; Sirajuddin; Amir, Aswita; Muhammad Ikhtiar; Horax, Ronny (Window of Health : Jurnal Kesehatan, 2024)
The condition of toddlers having less length or height based on age as a result of factors such as socio-economic conditions, maternal nutrition during pregnancy, and lack of nutritional intake in the first 1000 days of life is called stunting. Nutritional intake factors include failure to initiate breastfeeding, failure to provide exclusive breast milk, and the early weaning process. The research aims to determine the relationship between a history of early initiation of breastfeeding and exclusive breastfeeding with the incidence of stunting in children under two years aged 6-24 months. The research was conducted in the work area of ​​the Lere Community Health Center, Palu City. This type of research is observation with a case-control approach with chi-square analysis. The sample in this study was 19 stunted and 38 under two years old who were not stunted. Data is presented in table form accompanied by a narrative. The results of the research showed that from 57 samples, the percentage of stunting was 33.3%, those under two years old who received early initiation of breastfeeding was 47.4%, and those who received exclusive breast milk were 56.1%. The statistical test results show a significant relationship between a history of early and exclusive breastfeeding and the incidence of stunting in toddlers aged 6-24 months (p < 0.05) with an OR of 9.143 and 6.873, respectively. It is recommended that pregnant women initiate early breastfeeding immediately after giving birth and commit to providing exclusive breastfeeding to maintain the child's growth and development.